Utilization of performance indicators in data envelopment analysis to increase the efficiency discrimination of units. (July 2020) - Shahghobadi, Saeid
Highlights: Using performance indicators, a model is made with more discrimination capability. An efficiency frontier between the optimistic and pessimistic frontiers is made. By reducing the optimistic viewpoint, a cynical assessment has been used. The relative efficiency is calculated without solving any mathematical programming. Abstract: It is well- known that classic models of data envelopment analysis (DEA) evaluate decision-making units (DMUs) in the optimistic view, and therefore, the number of units known as efficient units is high. In order to increase the discrimination capability of the models, the evaluation of units in the worst case is also considered. In this case, units that are known to be efficient are either very low or not at all. In this paper, a method for performance assessment of units is introduced so that a large number of units are not evaluated as efficient, but there is at least one efficient unit. In this approach, a viewpoint between purely optimistic and pessimistic views is considered. The relative efficiency scores of units are directly calculated by using performance indicators without solving any linear or non-linear programming. Besides, the corresponding production possibility set (PPS) of the model is constructed. Illustrated examples are provided to compare production possibility sets and performance scores in all three perspectives.